Marketing pattern of rapeseed-mustard of three categories of farmers in Morena district of Madhya Pradesh - Shailendra Sharma; Rahul Singh; DUM Rao; Lakhan Singh (Journal of Oilseed Brassica, 2026)
Rapeseed-mustard is an important edible oilseed crop in India, being cultivated predominantly in the states ofRajasthan, Madhya Pradesh, Haryana, Uttar Pradesh, West Bengal and Gujarat. The present study wasundertaken to study the marketing pattern of rapeseed-mustard in Morena district of Madhya Pradesh, India.The sample of farmers included 75 farmers each of small, medium and large farmer categories, amounting to225 farmer respondents. The study found that the marketable and marketed surplus of rapeseed-mustardranged from 92.4% (small farmers), 95.6% (medium farmers) and 97.8% (large farmers) out of their totalproduction. But their income varied greatly as small farmers sold away 84.7% in the first two months; evenwhen the prices were lower, to meet urgent farm and family obligations. But medium and large farmers didnot resort to ‘distress sale’, but reaped better returns by storing, watching the market prices, and selling athigher prices in later months. Timely market information, storage and credit facilities may help small farmersreap better returns.